2009
DOI: 10.1063/1.3190492
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of the ability of density functionals to predict the planar-to-three-dimensional structural transition in anionic gold clusters

Abstract: As gold clusters increase in size, the preferred structure changes from planar to three-dimensional and, for anionic clusters, Au(n)-, the two-dimensional(2D)-->three-dimensional (3D) transition is found experimentally to occur between n=11 and n=12. Most density functionals predict that planar structures are preferred up to higher n than is observed experimentally, an exception being the local spin density approximation. Here we test four relatively new functionals for this feature, in particular, M05, M06-L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 98 publications
10
69
0
Order By: Relevance
“…In the full set of xc functionals that we tested, 14 depend on kinetic energy density and 28 do not, while 9 out of the 14 functionals that depend on kinetic energy density are exact for all structures, which suggests kinetic energy density makes the xc functionals more likely to be correct for predicting lowestenergy isomers. Similar findings were reported in previous work on gold clusters; in particular, Mantina et al, 92 Johansson et al, 93 and Ferrighi et al 94 studied the 2D-to-3D structural transitions (as functions of n) for singly charged gold clusters Au n + and Ag n − , and in this context Ferrighi et al provided an analysis of the connection of the kinetic energy density dependence to predictions of the 3D−2D competition. The gold clusters tend to be planar structures at small size but to be compact 3D structures at large size.…”
supporting
confidence: 66%
“…In the full set of xc functionals that we tested, 14 depend on kinetic energy density and 28 do not, while 9 out of the 14 functionals that depend on kinetic energy density are exact for all structures, which suggests kinetic energy density makes the xc functionals more likely to be correct for predicting lowestenergy isomers. Similar findings were reported in previous work on gold clusters; in particular, Mantina et al, 92 Johansson et al, 93 and Ferrighi et al 94 studied the 2D-to-3D structural transitions (as functions of n) for singly charged gold clusters Au n + and Ag n − , and in this context Ferrighi et al provided an analysis of the connection of the kinetic energy density dependence to predictions of the 3D−2D competition. The gold clusters tend to be planar structures at small size but to be compact 3D structures at large size.…”
supporting
confidence: 66%
“…Computations are performed within TURBOMOLE V6.4 [46] using density functional theory employing the def2-TZVP basis set (with the associated effective core potential def2-ecp) [47] and the Tao-PerdewStaroverov-Scuseria meta-GGA functional [48]. The suitability of such type of functionals for the investigation of gold clusters has been discussed before [49,50]. The calculated harmonic vibrational frequencies are uniformly scaled by a constant multiplication factor of 1.06 that is chosen based on the comparison of experimental and theoretical peak positions for the gold clusters.…”
Section: Theoreticalmentioning
confidence: 99%
“…Potential functions, such as Gupta potential [11][12][13], Murrell-Mottram (MM) potential [14], embedded-atommethod (EAM) potential [15], and Sutton-Chen (SC) potential [16,17], have played an important role in investigating the stable structures and structural evolution of gold clusters. Previously we compared three different potential model for gold clusters, i.e., Gupta potential and SC potential with experimental-fitted parameters and SC potential with DFT-fitted parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Small gold clusters Au n (n B 16) were analyzed using the density functional theory (DFT) at B3LYP level with a Lanl2DZ pseudopotential to understand the rules governing the structures obtained for the most stable clusters [2]. The transition from flat-cage (Au 15 and Au 16 ) to hollow-cage structure (Au 17 and Au 18 ) was found at Au 17 , and the variation from hollow-cage to pyramidal structure was recognized at Au 19 [7,8]. For medium-sized gold clusters, experimental and theoretical study showed that the structures of Au 36 -to Au 38 -were found to be core-shell type structures all with a tetrahedral four-atom core, and at Au 38 -the appearance of a fragment of the face centered cubic (FCC) bulk gold implied that the cluster-to-bulk transformation starts to emerge at the medium size range [9].…”
Section: Introductionmentioning
confidence: 99%